The Mellops strike oil - Ungerer, Tomi, 1931- (Phaidon Press, 2011)
While on a family picnic Mr. Mellops notices the mountain water has an awful taste, like oil. Soon, the intrepid Mellops embark on a quest that takes them to the library, the museum and eventually an oil field!